Analysis of ChatGPT responses to breastfeeding questions - Medeiros, Natan Viana; Alvim, Vitor Fernandes; Silva, Maria Teresa dos Santos; Grunewald, Sabrine Teixeira Ferraz (ABCS Health Sciences, 2025)
Introduction: Artificial intelligence tools are impacting medicine in a way that makes knowledge more accessible to both doctors and patients, but their absolute accuracy is still little studied. Objective: This study aims to evaluate the quality of responses provided by ChatGPT to potential inquiries from families regarding breastfeeding. Methods: A cross-sectional study was conducted through an online questionnaire with active Brazilian pediatricians (n=56) who expressed their opinions on ten pairs of questions and answers related to breastfeeding. Questions were formulated based on common doubts, and responses were obtained after submitting the queries to ChatGPT. The quality of responses was assessed on a scale of 1 to 5 points. Results: The findings revealed an average score exceeding 4.0 for all questions posed to the artificial intelligence regarding "Clarity of the provided answer" and "Conformity with current scientific knowledge." Regarding "I am satisfied with the presented response," participants rated ChatGPT responses above 4.0 for most questions. Most pediatricians agreed with the statement, "If I were responding to this question for a real patient, my answer would be different." Conclusion: Responses generated by ChatGPT received high satisfaction rates from the population of pediatricians who evaluated them, being considered clear and based on updated scientific knowledge. However, most pediatricians stated they would provide different responses to their patients.